ASSESSMENT OF STABILITY PARAMETERS FOR MULTIPLE TRAITS IN NEWLY DEVELOPED SINGLE CROSS HYBRIDS OF MAIZE (Zea mays L.) - Niranjan Kumar Chaurasia (Journal of Animal and Plant Sciences, 2023)
Due to climatic changes around the world, maize is currently exposed to a variety of biotic and abiotic pressures in time and place that affect the performance of maize hybrids. Plant breeders need genotypes that respond consistently and preferentially to different environmental conditions. The present investigation was carried out with seven inbred lines, twenty-one F1 hybrids which were developed through a diallel matting scheme, and three hybrid checks at six environments which comprise three locations and two crop growing seasons. The pooled analysis of variance indicated highly significant mean squares due to environments, genotypes, and genotype by environment interactions (GEI) for all the traits like Days to 50 per cent anthesis, days to 50 per cent silk, anthesis-silking interval, days to 50 per cent physiological maturity, plant height, ear height, ear length, ear diameter, kernel rows per ear, kernels per row, grains per plant, 1000-kernel weight, shelling per cent and grain yield per plant. The mean squares of analysis of variance for all the studied traits in maize over the six environments revealed highly significant due to genotypes, Env. + (G x Env.), environment (linear), and pooled deviation. The significant to highly significant mean squares due to G × E (linear) were observed for all the traits under study except for days to 50% anthesis and silking, plant height, ear length, kernels per row, and grains per plant. The higher magnitude of mean squares due to environment (linear) than the corresponding G × E (linear) were recorded for all the studied traits indicating that the linear response of environment accounted for a major part of the total variance. The estimates of environmental indices revealed that environment, E4 (Rabi 2019-20, BAU, Sabour) had highly positive, therefore E4 is considered the most favorable environment amongst the six environments for the expression of all the studied characters. The estimates of stability parameters for grain yield per plant revealed nine hybrids, namely, P1 × P2, P1 × P4, P1 × P5, P2 × P4, P2 × P5, P3 × P4, P3 × P5, P4 × P7, and P5 × P6 had high mean grain yield, unit regression coefficient (bi=1) and non-significant deviation from regression (S2di=0) indicating these hybrids were stable for this trait over the test environments.
Keywords: G × E Interactions; Multiple traits; Maize; Stability parameters; and Single cross hybrids